RESTRICTIVE AND NON RESTRICTIVE RELATIVE CLAUSE IN JOHN GRISHAM’S ROGUE LAWYER - Ni Putu Yunick Cahyani; I Nyoman Sedeng; I Nyoman Udayana (Universitas Pendidikan Ganesha, 2021)
This study entitled Restrictive And Non Restrictive Relative Clause In John Grisham’s Rogue Lawyer that focuses on what the types of the relative pronoun and its modify. The data were taken from a novel by John Grisham entitled; Rogue Lawyer. The documentation method was used in order to collect the data. In analyzing data, the descriptive qualitative method applied in this study. The theory that was applied in this study was the theory Quirk et. al. (1985) in his book A Comprehensive Grammar of The English Language. Based on the analysis, all the relative pronoun found in the novel; who, whose, whom, which ,that and zero pronoun. However in the non-restrictive relative clause that found in the novel mostly used the separation marker comma.